Innovative Materials : Engineering and Applications : Selected, peer reviewed papers from the 2014 International Conference on Material Engineering and Application, (ICMEA 2014), October 18-19, 2014, Hangzhou, China - Bhatnagar, Anil K. (Anil Kumar), 1942- (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 2014 International Conference on Material Engineering and Application, October 18-19, 2014, Hangzhou, China. The 100 papers are grouped as follows: Chapter 1: Composites, Materials Engineering and Technologies, Chapter 2: Functional Materials, Chapter 3: Luminescent and Optical Materials, Chapter 4: Polymer Materials Science, Chapter 5: Bio and Medical Materials Engineering, Applications, Chapter 6: Building and Constructions Materials, Applications, Chapter 7: Measurement, Detection and Test Procedures, Chapter 8: Materials Processing and Forming, Surface Engineering, Tools and Equipment, Chapter 9: Materials Design, Applications of Materials in Industry and Manufacturing.